Kaempferia galanga L.: Progresses in Phytochemistry, Pharmacology, Toxicology and Ethnomedicinal Uses - Wang, Si-Yu; Zhao, Hui; Xu, Hong-Tao; Han, Xiao-Dong; Wu, Yun-Shan; Xu, Fang-Fang; Yang, Xiao-Bo; Göransson, Ulf; Liu, Bo (Frontiers in Pharmacology, 2021)
K. galanga is an aromatic medicinal herb. It is locally to India and distributed in China, Myanmar, Indonesia, Malaysia, and Thailand. K. galanga is a Traditional Chinese Herb Medicine (TCHM), which has been applied to treat cold, dry cough, toothaches, rheumatism, hypertension and so on. In addition, it has been used widely as spices since its highly aromas. The aim of this review is to compile and update the current progresses of ethnomedicinal uses, phytochemistry, pharmacology and toxicology of K. galanga. All the data on K. galanga were based on different classical literary works, multiple electronic databases including SciFinder, Web of Science, PubMed, etc. The results showed that ninety-seven compounds have been identified from rhizome of K. galanga, including terpenoids, phenolics, cyclic dipeptides, flavonoids, diarylheptanoids, fatty acids and esters. Modern pharmacology studies revealed that extracts or secondary metabolites of the herb possessed anti-inflammatory, anti-oxidant, anti-tumorous, anti-bacterial, and anti-angiogenesis effects, which were closely related to its abundant ethnomedicinal uses. In conclusion, although previous research works have provided various information of K. galanga, more in-depth studies are still necessary to systemically evaluate phytochemistry, pharmacological activities, toxicity and quality control of this herb.